The World Book Encyclopedia. - World Book, Inc. (Chicago, IL : World Book, Inc., 2014)
"A 22-volume, highly illustrated, A-Z general encyclopedia for all ages, featuring sections on how to use World Book, other research aids, pronunciation key, a student guide to better writing, speaking, and research skills, and comprehensive index"--
v. 1. A -- v. 2. B -- v. 3. C-Ch -- v. 4. Ci-Cz -- v. 5. D -- v. 6. E -- v. 7. F -- v. 8. G -- v. 9. H -- v. 10. I -- v. 11. J, K -- v. 12. L -- v. 13. M -- v. 14. N, O -- v. 15. P -- v. 16. Q, R -- v. 17. S-Sn -- v. 18. So-Sz -- v. 19. T -- v. 20. U, V -- v. 21. W, X, Y, Z -- v. 22. Research Guide, Index.
Includes index.
oif 23/06/15
Ref.
Keywords: Encyclopedias and dictionaries